THU0052 Levels of inflammatory serologic biomarkers in HLA-B27 and HLA-B15 positive patients with spondyloarthritis. (15th June 2017) - Londono, J; Santos, AM; Rueda, JC; Peña, P; Briceño, I; Saldarriaga, E-L; Angarita, J-I; Calvo, E; Avila, M; Martinez-Rodriguez, N; Cubides, H; Parra, V; et al.
Abstract : Background: A main challenge in spondyloartritis (SpA) management was the availability of reliable biomarkers related with disease activity, or predicting joint damage and the response to treatment. Although erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) are currently used as biomarkers for disease activity, they lack sensitivity, specificity and reproducibility. With the understanding of SpA pathogenesis, additional biomarkers like metalloproteinase 3 (MMP-3), interleukin (IL)-1a, IL-6, lipopolysaccharide-binding protein (LBP), tumour necrosis factor a (TNFa), macrophage colony stimulating factor (M-CSF), interferon gamma (INF-g), IL-17 and IL-23, had been proposed Objectives: We aimed to evaluate the associations of MMP-3, IL-1a, IL-6, M-CSF, LPB, IL-17 and IL-23 levels in SpA patients positive for HLA-B27 or HLA-B15 Methods: 178 patients (100 men and 78 women) with SpA according to ASAS criteria were included in the study. HLA typing was performed by PCR using the Biorad® HLA-SSP ABDR plates. The levels of TNFa, IL-1a, IL-6, INF-g and IL-17 were measured by a cytometric bead-array (CBA Flex Set) using a FACS Canto II Flow CytometerÔ. Enzyme-linked immunosorbent assay (ELISA) was used to determine serum levels of IL-23, M-CSFand MMP-3. CRP and LBP levels were measured by chemiluminescence. Statistical analysis was made with SPSS v19. For comparison of quantitative variables with a normal distribution we used the Student's t -test. Categorical variables were presented in frequency charts and percentages, and the Chi-squared test and Fisher's exact test were used when necessary, for comparing groups. Two-tailed P-value <0.05 was considered statistically significant Results: Of the 178 patients, 70 were positive for HLA-B27, 34 for HLA-B15 and 74 had other HLA-B. According to ASAS classification criteria, 152 patients had axial SpA (axSpA) manifestations, 161 had peripheral SpA (pSpA) manifestations, and 148 patients had mixed axial and peripheral manifestations. Figure 1 shows the mean levels of inflammatory serologic biomarkers in these subgroups of patients Conclusions: High levels of IL-17 and IL-23 were associated with the presence of HLA-B27, which mainly correlates with an axial presentation of the disease as compared to HLA-B15 patients. Accordingly, the genotype (presence of HLA-B27 or HLA-B15) and phenotype (axial or peripheral involvement) may help physicians when considering a targeted therapy of SpA patients with IL-17 inhibition in a context of personalized medicine Disclosure of Interest: None declared